Cimarinjung River Water Quality Study in Ciwaru Village Ciletuh Geopark Area, Sukabumi Regency, West Java - Putri, Ifti Nanda; Syahrani, Yasinta; fitriyah, faizah nur; Dahlia, Siti; Ramadhan, Dwi; Fadjriani, Aida; Hartono, Dwi Ari; Hofifah, Erni; Nadhira, Faizzati; Putri, Ika Tiana; Ristiadi, Rakina; Susilawati, Yeti (JPG (Jurnal Pendidikan Geografi), 2024)
This study aims to determine the water quality of the Cimarinjung River in the Ciletuh Geopark area, Ciwaru Village. The method used in the study was a survey method by taking samples at one location of Cimarinjung River water samples. The results of the study found that the water quality of the Cimarinjung River had some parameters that did not meet the standards required in the water quality standards in Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Management (Appendix VI concerning Class 1 National Water Quality Standards). Shown by water quality in physical parameters, namely the total solids are sorted by 1369 mg/l which is not in accordance with the requirements (1000 mg/l). The water quality for chemical parmeter, chloride (Cl), was 9340 mg/l exceeding the required limit (300 mg/l). The quality of the biological parameter is APM Esherichia Coli 350 APM/100 ml which exceeds the required limit (100 APM/100 ml).